دراسة سيفالومترية لتغييرات الزاوية بين الفكية وعلاقتها بالازدحام الثالثي. - خليل, فادي حسن; المنجد, محمد قصي; عبيدات, سامي عبدالله (Latakia University Journal -Medical Sciences Series, 2019)
يعد الازدحام الثالثي مشكلة شائعة في الممارسة التقويمية تنعكس سلبا على تقدير مدى الحاجة للتثبيت بعد المعالجة التقويمية للمرضى، الأمر الذي يستنزف الوقت والجهد لكل من الطبيب والمريض. فنحن في بحثنا هذا تناولنا 74 مريضا لديهم ازدحام ثالثي وصنف أول هيكلي وتم قياس الزاوية بين الفكية لديهم لدراسة الارتباط بين الازدحام الثالثي والدورانات الفكية السفلية من خلال تغييرات الزاوية بين الفكية؛ للوصول إلى احد العلامات التشخيصية التي من الممكن أن تساعد في تقصي احد أسباب الازدحام الثالثي, و تبين من خلال النتائج التي حصلنا عليها بعد إجراء التحاليل الإحصائية الخاصة بهذه الدراسة وجود الارتباط بين الازدحام الثالثي والدوران الأمامي للفك السفلي وذلك في الحالات التي تكون فيها الزاوية ما بين الفكية أقل من الطبيعي. The tertiary crowding is considered a common problem in the orthodontic practice that negatively influences assessment of the need for retention following the orthodontic therapy for patients, wasting the time of both patients and doctors. In this paper we covered 74 patients with tertiary crowding and skeletal first class; the intra-mandibular angle in these patients was measured by manual drawing of the cephalometric photos of these patients for detecting the correlation between the tertiary crowding and the mandibular rotations by the variations in the intra-mandibular angle with the aim to reveal one of the diagnostic signs that may assist to investigate one of the causes of tertiary crowding . In the light of the outcome we had, after conducting the related statistical calculations, we prove the correlation between tertiary crowding and the mandibular anterior-rotation in cases when the intra-mandibular angle is less than normal .